DIPG-13. A NOVEL MOUSE MODEL REVEALS UNEXPECTED MECHANISMS OF ACTION OF ACVR1 MUTATIONS IN DIFFUSE INTRINSIC PONTINE GLIOMA. (23rd April 2019) - Fortin, Jerome; Tian, Ruxiao; Zarrabi, Ida; Hill, Graham; Williams, Eleanor; Sanchez-Duffhues, Gonzalo; Thorikay, Midory; Ramachandran, Parameswaran; Siddaway, Robert; Wong, Jong; Haight, Jillian; You-Ten, Annick; et al.
Abstract: Diffuse Intrinsic Pontine Gliomas (DIPGs) are aggressive pediatric brain tumors for which there is currently no effective treatment. Most DIPGs are driven by mutations in histone H3-encoding genes, and a subset of these tumors also carry gain-of-function mutations in ACVR1, which encodes a BMP type I receptor. The oncogenic mechanisms of action of these ACVR1 mutations are currently unknown. Here, we generate a novel conditional knock-in mouse model of the most common ACVR1 mutation driving DIPG ( Acvr1 G328V ). Glial cells carrying the mutation hyperactivate BMP signaling, exhibit enhanced proliferation, and expand throughout the brainstem in vivo . Unexpectedly, we observe that the Acvr1 G328V mutation is sufficient to trigger an arrest in the differentiation of oligodendroglial lineage cells, a hallmark event in the formation of many types of gliomas including DIPGs. Mechanistically, this differentiation block is associated with upregulation of transcription factors that control the development of glial progenitors. Inactivation of these factors, which are highly expressed in human DIPGs, impairs the growth of patient-derived DIPG cells and enhances their sensitivity to treatment with a novel ACVR1 inhibitor. Collectively, our results describe a potential oncogenic mechanism of action for ACVR1 mutations, and suggest new therapeutic strategies for the treatment of DIPG.